An Approach to Assess Land Stability and Erosion on Mined Landforms - Devika Nair; Sean Bellairs; Kenneth G. Evans (Mining)
Where mining activities cause disturbance in catchments, streams are often impacted by heavy loads of fine eroded material. Since geomorphological processes are very slow, it is expected that during rehabilitation, typically hundreds of years are required for a mine landform to return to stability. A sensitive approach to analyzing post-mining landform stability in tropical regions is to assess the quantity of fine suspended sediments (FSS = silt + clay (0.45 µm < diameter < 63 µm)) leaving the catchment where the mine resides and entering the receiving streams in response to storm events. Continuous stream discharge and FSS quantities upstream and downstream of the catchment where the mine resides were modeled using the HEC-HMS (Hydrologic Engineering Centre–Hydrologic Modeling System). Once calibrated, the model was run for a thousand years to predict continuous stream discharge and FSS quantities for various predicted rainfall scenarios. Short-term erosion and deposition across the mine catchment were also evaluated using a calibrated landform evolution model, CAESAR-Lisflood. This paper reviews watershed soil erosion measurements and modeling research leading to the abovementioned approach. This approach assesses mine landform erosion and stability in terms of fine suspended sediments. It can be used to determine mine landform erosion dynamics, predict the achievement of landform stability equilibrium, and as a post-mining rehabilitation assessment tool.